A Carleman estimate for the linear magnetoelastic waves system and an inverse source problem in a bounded conductive medium. Issue 14 (25th October 2020) - Bellassoued, Mourad; Moufid, Chaima; Yamamoto, Masahiro
ABSTRACT: In this paper, we consider an inverse problem for the simultaneous diffusion process of elastic and electromagnetic waves in an isotropic heterogeneous elastic body which is identified with an open bounded domain. From the mathematical point of view, the system under consideration can be viewed as the coupling between the hyperbolic system of elastic waves and a parabolic system for the magnetic field. We study an inverse problem of determining the external source terms by observations data in a neighborhood of the boundary and we prove the Hölder stability. For the proof, we show a Carleman estimate for the displacement and the magnetic field of the magnetoelastic system.